Perancangan Tata Kelola TI Menggunakan Framework COBIT 2019 pada Pusat Data dan Informasi Kementerian XYZ - Afdhani, Rizqi; Soewito, Benfano (Universitas Komputer Indonesia, 2024)
The Data and Information Center (Pusdatin) is one of the organizational units of a government institution responsible for managing Information and Communication Technology (ICT) in the Ministry XYZ. Many issues have been identified in the development and management of information systems by Pusdatin of the Ministry XYZ due to the absence of proper IT governance standards. Therefore, IT governance is needed to optimize the use of technology within the agency to support the goals of Pusdatin of the Ministry XYZ. This research uses the COBIT 2019 framework, which is the latest version of COBIT released by ISACA. The aim of this study is to assess the capability levels, determine gap values, and provide recommendations for an IT governance framework in Pusdatin of the Ministry XYZ based on the COBIT 2019 framework. The research method includes literature review, observations, and interviews following the COBIT 2019 Design Guide. The mapping results identify three priority domains: APO09 (Managed Service Agreements), BAI10 (Managed Configuration), and DSS01 (Managed Operations). The measurements capability levels show that all three domains are currently at level 1, while the target is level 4, indicating a significant gap. Improvement recommendations are provided for IT governance activities based on COBIT 2019 best practices for each domain. The highest priority is given to improving BAI10 to establish a strong configuration management foundation, followed by enhancing IT operational processes through DSS01 and improving user satisfaction with a focus on IT services through APO09